Johnson & Johnson's financial health status assessment: based on the comprehensive financial statement analysis - Lin, Xiaowei (Transactions on Economics, Business and Management Research, 2024)
With the development of society and the improvement of people's living standards, a healthy life has been paid more and more attention. However, some insurmountable viruses are like obstacles to the road, threatening people's health. How to deal with these viruses and how to ensure human health and safety have become an urgent problem to be solved. Founded in 1886, Johnson & Johnson Company, as a well-known enterprise with a history of one hundred years, firmly believes that its core values come from the corporate creed. Over the years, Johnson & Johnson has always been committed to social feedback and taking practical actions to practice corporate value. Johnson & Johnson topped the 2020 list of the world's most valuable pharmaceutical companies. The success of Johnson & Johnson is closely related to its continuous innovation and pioneering spirit. The company's continuous innovation in medical devices, drugs, consumer health products and other fields makes Johnson & Johnson always maintain the leading position in the industry. This paper first discusses the development process and business strategy of Johnson & Johnson, and then systematically evaluates the business performance of Johnson & Johnson from both theoretical and empirical aspects. Based on the principle of selection indicators such as rationality and comparability,In order to study the financial statements of Johnson & Johnson, this paper selects a variety of indicators such as sales gross profit margin, net interest rate of total assets, inventory turnover, current assets turnover and total assets turnover for analysis, and uses DuPont analysis method. As a result of the analysis, in the past two years, the performance of Johnson & Johnson has been mediocre, and it is necessary to adjust the management to improve the asset management efficiency and operating capacity, so as to increase the profit margin to enhance the development capacity.